Indonesia - Investing in the future of Papua and West Papua : Infrastructure for sustainable development - World Bank (World Bank, 2012)
The remote and sparsely populated provinces of Papua and West Papua face a time of great change. Monetary transfers from Jakarta have grown extraordinarily in recent years, by more than 600 percent in real terms and 1300 percent in nominal terms since 2000, greatly increasing demand for goods and services. The high price of imports in the interior is producing pressure to improve roads in order to lower transport costs. Pressure is mounting to open up the interior of the region to commercial interests that would like to extract resources: copper, gold, coal, petroleum, natural gas, and, above all, timber. Investment in infrastructure, especially in road transport, is seen as the means to make dreams of development a reality. Building infrastructure in Papua and West Papua also is challenging because of physical (i.e. topographical and geological) conditions. Much of the region has either poorly drained peat soils or steep slopes with thin soils subject to landslides and erosion. Most of Papua and West Papua also receive heavy seasonal rainfall. The cost of building a good, well-planned road into the highlands is Indonesian Rupiah (IDR) 6 to 10 billion per kilometer, far more than has been budgeted in the past. Combined with the low population density (a region three times the size of Java has a population smaller than that of Lombok), this means that it takes bigger networks of roads and power to serve the population. Moreover, such infrastructure has been inadequately maintained. As a result, especially outside urban areas, there is too little to show for past investments in roads, water supply systems, or power generating capacity. The aim of this report is: (i) to lay out the challenges that faces infrastructure planners and implementers in the central, provincial, and Kabupaten and Kota governments in a clear manner; and (ii) provide those planners and implementers with recommendations, based on the best information available, on how to mitigate the effects of these challenges.